AI smart kit : agile decision-making on AI (abridged version) - Stephens, Melodena; Vashishtha, Himanshu (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"There are many myths about Artificial Intelligence (AI) relating to what it is and what it can and cannot do. Very often, the people taking decisions on AI projects are not technologically savvy and not able to find easy answers. The spending on and the returns from AI projects are not necessarily clear and part of the reason for this is the lack of understanding on key decision criteria. AI touches on many ethical concepts - data privacy, validity and more importantly, its potential misuse. AI is often being used to replace human decision-making and there is often no real understanding of the implications of this. This book provides an easy and accessible guide for practitioners without a technological background. It guides the reader through the basic issues and offers advice on 'how to take decisions' and 'ask relevant questions' through the inclusion of 15 decision scales. There is currently no comparable book on the market and it is therefore likely to be widely read"-- Provided by publisher.
Keywords: Artificial intelligence.; Decision making.; Computers -- Artificial Intelligence -- General.; elektronické knihy; electronic books